CLINOPYROXENE COMPOSITION AND GENESIS OF BASALTS FROM COLOURED SERIES AND EXOTIC BLOCKS IN THE NEYRIZ AREA (SOUTHERN IRAN): A COMPARISON WITH HAYBI COMPLEX OF OMAN (Journal of Sciences, Islamic Republic of Iran)
The pyroxene composition of basaltic rocks from the Coloured Series and Exotic blocks in the Neyriz area are discussed. Comparison has been made with equivalent rocks from Oman. The clinopyroxene compositions are in cognation with trace and rare-earth element analyses which definately confirm the occurrence of three different trends in basic lavas: I-Depleted tholeiite, 2-Transitional basalt, 3-Alkali basalt. The alkali basalts are considered to be generated by the same processes that produce tholeiitic liquids but are thought to have had a different fractionation history